CityCapt: Inovasi Teknologi Carbon Capture Direct Air and Biological Capture Guna Mendukung Pencapaian SDGs 2030 - Rahma Khusniawati; Muhammad Sholeh Al Ghifari; Wafi Mumtaz Malik; Yasa Palaguna Umar (Prosiding ESEC, 2023)
Several mitigation options, Carbon Capture Utilization and Storage (CCUS) technology is estimated to have sustainable potential to reduce CO2 emissions. Various CCUS technologies that have been developed include DAC (Direct Air Capture) and BC (Biological Capture). However, these existing technologies have shortcomings including technological efficiency that is not in line with the initial design and the price for the technology is quite expensive. CityCapt is an innovation of DAC technology integrated with BC for CO2 absorption in open spaces such as city halls, parks and other public places. This technology is operated with fuel from solar panels with the principle of capturing CO2 from ambient air, then channeled to microalgae containers for biological processing. CO2 that enters the microalgae container will become a source of energy for microalgae which can then be harvested to be used as biomass so as to optimize technology and reduce operational costs. With this technology, CO2 generated from urban activities can be captured, managed and utilized as a renewable energy source.